Effect of Increasing Povidone-Iodine Exposure on Corneal Epithelium and Impact on Donor Rim Cultures. Issue 12 (24th December 2022) - Sawant, Onkar B.; How, Stephanie; Hurlbert, Susan; Titus, Michael S.; Vadakkepattath, Indu; Shen, Xiang; Djalilian, Ali R.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Purpose: The purpose of this study was to assess the effect of a second povidone-iodine (PVP-I) application at the time of donor tissue recovery on overall tissue quality and to analyze the rate of positive fungal and bacterial rim cultures before and after implementing increased PVP-I exposure. Methods: The left cornea was recovered after a single application of PVP-I, while the right cornea was recovered after double PVP-I application in research-consented donors. The epithelial cell death rate was estimated using viability assay in corneal whole mounts under 10× objective (n = 5). Clinical characteristics of epithelium, stroma, and endothelium; positive rim culture rate; and incidences of infectious postoperative adverse reactions were compared for a period of 14 months before and after implementation of increased PVP-I protocol. Results: The average epithelial cell death rate was unaltered between single and double PVP-I exposure groups. We observed a modest 10% increase in the number of tissues with mild edema after implementation of increased PVP-I exposure. Nonetheless, the percentage of tissues with moderate or severe edema was unaltered. The average positive rim culture rate decreased from 1.17% to 0.88% ( P = 0.075) after implementation of the double PVP-I soak procedure. There has been only one report of infectious postoperative adverse reactions since this procedure change. By contrast, there were 5 reports for a period of 14 months before implementation of this protocol. Conclusions: These results indicate that new donor preparation methods with an additional 5 minutes of PVP-I exposure do not affect tissue quality, reduce positive rim cultures, and lead to lower incidence of postoperative infection.